The Cluster Design and Redox Behavior Characterization of Polyoxometalates for Redox Flow Batteries. Issue 24 (14th November 2022) - Han, Yanhong; Lan, Jinji; Li, Ke; Yang, Le; Zhu, Chengxiang; Chen, Jiajia
Abstract: Polyoxometalates (POMs) are a class of metal‐oxygen cluster molecular materials formed by covalently linking transition metal atoms and oxygen atoms. Those molecular cluster materials also shows multiple electron reversible redox capabilities and high solubility in solution. Thus, POMs also recently present interesting applications as redox active electrolyte in redox flow batteries (RFBs). In this review, we mainly focus on the structural design of POMs and analysis factors affecting the electrochemical properties of POMs. Spectroscopic characterizations are introduced to deeply explore the structural changes of POMs during the redox process. Furthermore, we summarize the cases of POMs used as liquid‐phase redox couple in aqueous or non‐aqueous redox flow batteries and discuss the advantages and deficiency of POMs with various configurations. Abstract : In this Review, we briefly introduce the structure design and synthesis process of redox active POMs. Next, in‐situ and ex‐situ characterization methods for structural studies are summarized. After that, a detailed introduction of POM‐based aqueous and non‐aqueous RFBs is given. We also briefly summarize the challenges and prospects in the current research field.